Crack initiation and endurance limit of hard steels under multiaxial cyclic loads - Bomas, H.; Kienzler, R.; Kunow, S.; Loewisch, G.; Schroeder, S. (Проблемы прочности, 2008)
The endurance limit and the mechanisms o f fatigue crack initiation in the high cycle regime were investigated using round specimens o f the bearing steel 52100 under longitudinal forces and torsional moments and combinations o f these loads. Three specimen types were examined: smooth specimens and specimens with circumferential notches with radii o f 1.0 and 0.2 mm. The influence ofmean and multiaxial stresses on the endurance limit can be understood by consideration ofcrack initiation mechanisms and micro-mechanics. Crack initiation took place at oxides, carbonitrides and at the surface. The mechanisms ofcrack initiation could be related to the load type: Loads with rotating principal stresses are more damaging fo r nitrides than fo r oxides. Increasing maximum stresses are more dangerous fo r nitrides than fo r oxides, and introduce more damage to the surface than to the nitrides. Normal stresses are more damaging fo r oxides than shear stresses. The endurance limits were calculated by means o f an extended weakest-link model which combines volume and surface crack initiation with related fatigue criteria. For volume crack initiation the criterion o f Dang Van was used. For the correct description o f the competing surface crack initiation, a new criterion was applied. With this concept, a prediction o f the endurance limit is possible fo r loads which produce critical planes and range within a limited regime ofstress ratios.